Br̥hattara Dinājapurera āñcalika gāna : Pañcagaṛa, Ṭhākuragām̐o o Dinājapurera gāna - Raśīda, Hārunura, 1975- (Ḍhākā : Janapriẏa Prakāśanī, 2022)
Collection of texts of Bengali folk songs of grater Dinājpur District of Bangladesh.
Texts of songs.
Saṃgrāhaka, Śaphikula Isalāma, Praśānta Basāka, Āminula Isalāma.
In Bengali.
Keywords: Folk songs, Bengali -- Bangladesh -- Dinājpur District -- Texts; Chansons folkloriques bengali -- Bangladesh -- Dinājpur (District) -- Textes; Folk songs, Bengali; Bangladesh -- Dinājpur District; Texts; Folk song texts; Paroles (Chansons folkloriques)